Red Rice Bran Ethanol Extract Reduces IL-1β as the Risk of Pancreas Fibrogenesis in Type 2 Diabetic Rat Model - Brian Wasita; Ratih Dewi Yudhani; Dyonisa Nasirochmi Pakha; Diana Nurrohima; Muthmainah Muthmainah; Nanang Wiyono; Shariza Fakurazi (Indonesian Biomedical Journal, 2025)
BACKGROUND: Oxidative stress and inflammation contribute to pancreatic cell dysfunction that promote insulin resistance in type 2 diabetes (T2D). Red rice bran contains bioactive substances with anti-inflammatory and antioxidant properties which improved insulin resistance in obese mice. However, no studies have explored the potential of ethanol extract of red rice bran (EERRB) to prevent T2D progression, particularly pancreatic fibrosis complications. This study was conducted to investigate the effect of EERRB on inflammation measured with interleukin (IL)-1β and fibrosis of pancreatic tissue in a rat model of T2D.